Imaging techniques for the diagnosis of soft tissue tumors - Afonso, Diana; Mascarenhas, Vasco (Reports in medical imaging, 2015)
The primary aim in soft tissue tumor imaging should be to reach a specific diagnosis or to narrow the differential diagnosis, and to help to decide whether biopsy, surgical intervention, or simple observation is required for further management. In addition to contributing toward diagnosis, imaging has an important role in the staging of soft tissue malignancies and potentially in response assessment. This general review article highlights a rational diagnostic imaging approach to patients presenting with soft tissue tumors, emphasizing the fundamental principles inherent to soft tissue tumor imaging and diagnosis.